Transcriptomic analysis of selenium accumulation in Puccinellia distans (Jacq.) Parl., a boron hyperaccumulator. (April 2020) - Kök, Aysu Başak; Mungan, Mehmet Direnç; Doğanlar, Sami; Frary, Anne
Abstract: Selenium (Se) is present in a wide variety of natural and man-made materials on Earth. Plants are able to tolerate and (hyper)accumulate Se to different extents. In fact, some species can tolerate and accumulate multiple elements. Puccinellia distans ( P. distans ), weeping alkali grass, is known to hyperaccumulate extreme concentrations of boron and tolerate high levels of salinity, therefore, we investigated the Se accumulation and tolerance capacities of this species. In addition, P. distans' Se tolerance mechanism was studied using a transcriptomic approach. The results of this study indicated that, when grown in a hydroponic system containing 80 or 120 μM Se, P. distans shoots accumulated from 1500 to 2500-fold more Se than plants grown without the element. Thus, P. distans was discovered to be a novel Se accumulator plant. RNA sequencing results and biochemical analyses helped to shed light on the Se tolerance and accumulation mechanism of P. distans . Here, we suggest that upregulation of Se assimilation and stress response genes may be due to induction of jasmonic acid signaling. In addition, we propose that the cell wall may play an important role in restriction of Se movement to the cytoplasm. Also, we hypothesize that Se accumulates in cells by sequestration of selenate in the vacuole. Highlights: Puccinellia distans is a selenium accumulator. Accumulation results in many transcriptomic changes. Sulfur and selenocompound metabolism are up-regulated. Reactive oxygen species are produced and glutathione metabolism is altered. Jasmonic acid synthesis is induced.